Peran Brand Image: Pengaruh Celebrity Endorsement, E-WOM, dan Perceived Quality terhadap Purchase Intention Skincare pada Gen-Z - Fahlevi, Renza; Helen, Helen; Sinambela, Fitriana Aidnilla (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This study aims to explore the impacts of Celebrity Endorsement in terms of Attractiveness, Trustworthiness, and Expertise, E-WOM, and Perceived Quality on Purchase Intention of local skincare products among Gen Z consumers, with Brand Image as a mediator. The research adopts a quantitative approach and explanatory method. Samples are selected using purposive technique within non-probabilistic methods. Data are collected through questionnaire surveys, with a total of 300 respondents. The gathered data will be analyzed using SmartPLS and SPSS. The findings reveal that E-WOM and the credibility of celebrity endorsements significantly impact the local skincare brand image among Gen Z. Perceived quality and brand image also play a significant role in enhancing purchase intention. Furthermore, it is found that brand image acts as a mediator in the relationship between E-WOM and celebrity endorsement, ultimately enhancing purchase intention of local skincare among Gen Z consumers.